2015
DOI: 10.1007/s00520-014-2576-6
|View full text |Cite
|
Sign up to set email alerts
|

Applicability and evaluation of a psychosocial intervention program for childhood cancer patients

Abstract: This psychosocial intervention for childhood cancer patients appears to be applicable. Future studies need to establish whether this intervention combined with a physical exercise intervention actually improves psychosocial functioning of childhood cancer patients. When proven effective, this combined intervention can be offered to childhood cancer patients and may enhance their physical health and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 24 publications
0
20
0
6
Order By: Relevance
“…In the 33 included papers, 24 interventions were evaluated. Four interventions were each investigated in two or more papers (Group Social Skills Intervention Program [ 47 50 ], Surviving Cancer Competently Intervention Program [ 51 , 52 ], Quality of Life in Motion [ 53 , 54 ], Family oriented rehabilitation [ 55 59 ]). However, the samples or the focuses of the articles differ and some interventions have been revised over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 33 included papers, 24 interventions were evaluated. Four interventions were each investigated in two or more papers (Group Social Skills Intervention Program [ 47 50 ], Surviving Cancer Competently Intervention Program [ 51 , 52 ], Quality of Life in Motion [ 53 , 54 ], Family oriented rehabilitation [ 55 59 ]). However, the samples or the focuses of the articles differ and some interventions have been revised over time.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies was conducted in North America or Europe (85%, n = 28) [ 47 65 , 68 , 71 77 , 79 ]. Most of the studies were intervention studies without a control group and with at least two measurement time points (n = 15) [ 47 , 50 , 51 , 53 , 55 , 57 , 59 , 61 , 64 , 65 , 72 , 73 , 76 , 77 , 79 ]. Eight papers reported randomized controlled trials [ 48 , 52 , 54 , 66 70 ], six papers described non-randomized controlled intervention studies [ 49 , 56 , 58 , 63 , 75 , 78 ], and four papers reported uncontrolled cross-sectional intervention studies [ 60 , 62 , 71 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The psychosocial training consists of psycho‐education and cognitive‐behavioral techniques covering the following topics: increasing self‐awareness and self‐belief; expressing positive characteristics about oneself; core feelings of fear, anger, happiness and sadness; feelings, thoughts and behavior; coping with (non) disease‐related difficult situations; relaxation exercises; possible changes in social contacts with peers, sexuality and relationships (for adolescents); possible changes in relation with parents and siblings; looking toward the future in general and plans to continue physical exercises in daily life. The psychosocial training appeared applicable with good adherence rates and positive evaluations by patients and psychologists .…”
Section: Methodsmentioning
confidence: 96%
“…To our knowledge, interventions using Facebook groups have not targeted families of pediatric brain tumor patients specifically or childhood cancer patients more broadly. Several online [51,52] and offline [53][54][55] interventions for the parents of children affected by cancer have been conducted and have shown encouraging results for psychosocial outcomes such as depression, anxiety, post-traumatic stress symptoms, and family functioning. Parent adherence and satisfaction with the Facebook group component of this intervention suggests a cost-effective addition to these already promising models.…”
Section: Discussionmentioning
confidence: 99%